(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Labour welfare means the effort to make the life comfortable for the workers. Key objective behind providing welfare measures is that workers obtain satisfaction which would ultimately lead to better productivity. Welfare activities will go along way to better the mental and moral health of workers by reducing vices of industrialization. India which launched a boat of social security sometime in the second half of the nineteen century has still been in troubled waters and is far awayfrom the cherished goal of full social security for her citizens. So this study is conducted to know whether the workers are aware and satisfied with the welfare facilities provided by textile industry in punjab as the textile industry is the single largest manufacturing industry of India which had a st rong impact on the development of the labour and trade union movement in India. The study is conducted to make some suggestions for betterment of workers in future because the successful implementation of labour welfare activities are an extension of democratic values in an industrialized society.